CONVERGENT VALIDITY OF THE SECOND VERSION OF THE MULTIDIMENSIONAL SOCIAL CAPITAL SCALE (MSCS V2) - Zariņa, Ieva; Šuriņa, Sanita; Perepjolkina, Viktorija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
Studies show that social capital has a positive effect on a person's mental health and subjective well-being. Recently, a second version of the Multidimensional Social Capital Scale (MSCS V2) has been developed in Latvia. The aim of this study is to verificate the psychometric properties of the MSCS V2 and to investigate its relationship to self-reported measures of loneliness and subjective well-being. Data was collected online between June 11th and October 3rd, 2021. Participants (N=353, aged between 18 and 80 years (M = 41.8, SD = 13.18), 87% females and 13% males) in addition to the MSCS V2 were asked to complete the UCLA Loneliness Scale Version 3, the Satisfaction with Life Scale (SWLS), and the Scale of Positive and Negative Experience (SPANE). The results show: the Cronbach alpha of the MSCS V2 scales meets the scientific requirements ranged from .73 to .90; Corrected Item-Total Correlations for all MSCS V2 scales are acceptable ranged from .53 – .81 and reaction indexes fall within the range of 2.67 to 4.48; a statistically significant negative association between the MSCS V2 scales and the UCLA Loneliness scale; statistically significant positive association between the MSCS V2 scales and the SWLS; statistically significant positive association between the MSCS V2 scales and the SPANE. The convergent validity of the scale was demonstrated by negative correlations with self-reported loneliness and positive correlations with subjective well-being measures.